Interaction of mouse macrophage elastase with native and oxidized human alpha 1-proteinase inhibitor. - Banda, M J (1987)
Native and oxidized alpha 1-proteinase inhibitor (alpha 1-PI) were compared as substrates for the metalloproteinase macrophage elastase. At substrate concentrations at which native alpha 1-PI was readily degraded by macrophage elastase, oxidized alpha 1-PI was hardly degraded at all. Incubation of macrophage elastase with oxidized alpha 1-PI before the addition of native alpha 1-PI showed that oxidized alpha 1-PI was not an inhibitor of macrophage elastase. Competition experiments with up to twofold excess oxidized alpha 1-PI did not interfere with the degradation of native alpha 1-PI by macrophage elastase. Sequence analysis of amino acids in degraded native alpha 1-PI showed that macrophage elastase attacked a single peptide bond between Pro-357 and Met-358, the latter representing the P1 reactive-site residue of alpha 1-PI. In oxidized alpha 1-PI, Met-358 was converted to methionine sulfoxide and macrophage elastase hydrolyzed the bond between Phe-352 and Leu-353. These data suggest that methionine may be the primary cleavage site for macrophage elastase and not leucine, as previously thought.